THE RISING GOVERNMENT EXPENDITURE IN NIGERIA: ANY INFLUENCE ON GROWTH? - Awode, Segun Subair (The European Journal of Applied Economics, 2019)
This study attempts to examine whether government expenditure in Nigeria has had any influence on growth in the economy. The study focuses primarily on capital and recurrent types of government expenditure, and these were regressed against the real gross domestic product. Secondary time series data ranging from 1981 to 2016 obtained from the CBN Statistical Bulletin were used. Having established that the series were co-integrated in the long run through the Cointegration technique of Johansen, the study then used the error correction and Granger causality techniques to achieve its objectives. Results indicated that recurrent expenditure exerts a significant positive influence on real GDP, while the influence of capital expenditure on real GDP turned out negative. The Granger causality test revealed that both capital and recurrent expenditures Granger cause real GDP. The study, therefore, advocates for a strong monitoring and evaluation system of the way in which government funds, especially those intended for capital projects, are being used, so as to bring about a meaningful influece on the economy.